1999
DOI: 10.1021/bp9900256
|View full text |Cite
|
Sign up to set email alerts
|

Stable High-Copy-Number Integration of Aspergillus oryzae α-AMYLASE cDNA in an Industrial Baker's Yeast Strain

Abstract: The Aspergillus oryzae alpha-amylase cDNA was placed under the control of the Saccharomyces cerevisiae actin promoter (pACT1) and introduced into the ribosomal DNA locus of an industrial baker's yeast strain. To obtain a strain eligible for commercial use, we constructed an integrative cassette lacking bacterial DNA sequences but containing the alpha-amylase cDNA and ribosomal DNA sequences to target the integration to this locus. High-copy-number integrants were obtained including a defective TRP1d promoter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 17 publications
1
39
0
2
Order By: Relevance
“…These vectors are the first of their kind for Y. lipolytica and are the third example of this type. Such integrative cassettes devoid of bacterial DNA which could be amplified have also been used for the expression of Aspergillus oryzae ␣-amylase in an industrial baker's yeast strain (29) and for the expression of monellin in Candida utilis (17).…”
Section: Discussionmentioning
confidence: 99%
“…These vectors are the first of their kind for Y. lipolytica and are the third example of this type. Such integrative cassettes devoid of bacterial DNA which could be amplified have also been used for the expression of Aspergillus oryzae ␣-amylase in an industrial baker's yeast strain (29) and for the expression of monellin in Candida utilis (17).…”
Section: Discussionmentioning
confidence: 99%
“…An additional advantage of these "defective" markers is that they may avoid protein-burden effects (39) due to massive overexpression of the marker gene. Both LEU2d and TRP1d markers have been used successfully to obtain high copy numbers of plasmid-borne as well as integrated expression cassettes (29,30).…”
Section: Applications Of Auxotrophic Yeast Strainsmentioning
confidence: 99%
“…Residual starch was determined to be 5% (w/v) after 3 days of fermentation and 3.6% (w/v) after 6 days of fermentation, respectively. This result indicates that the increase in the activity of glucoamylase via rDNA integration of the GA1 genes results in the improvements of raw starch degradation to glucose and of ethanol fermentation (Nieto et al, 1999). Yamada et al (2010) has reported that a tetraploid strain of S. cerevisiae that secretes Streptococcus bovis α -amylase to hydrolyze raw starch and Rhizopus oryzae glucoamylase produced 70 g ethanol/L after 3 days of fermentation.…”
mentioning
confidence: 91%
“…These values were 1.2-times and 1.9-times higher than the respective activities of the parental strain (Kim et al, 2011). The additional multicopy rDNA-integration of the GA1 or AMY genes can be correlated with the high-level expression of the corresponding genes (Nieto et al, 1999;Choi et al, 2002). The increase in activities of glucoamylase in addition to α-amylase is necessary for the more complete degradation of raw starch into glucose units, and consequently, more efficient ethanol production (Shigechi et al, 2004;Sun et al, 2010).…”
mentioning
confidence: 96%
See 1 more Smart Citation